Seroepidemiological study of leptospirosis among the indigenous communities living in the periphery of Crocker Range Park Sabah, Malaysia - Abdul Karim, Russ; Isam, El Jali; Abdul Rani, Bahaman; Andrew Alek, Tuen; Ghazally, Ismail (SEAN Review of Biodiversity and Environmental Conservation (ARBEC), 2003)
Leptospirosis has been known to affect both man and animal worldwide resulting in morbidity and mortality. Infection in domestic animals and wildlife can lead to economic loss and pose a potential spread to the communities. Man contacted the disease by direct contact with infected blood, tissues, organs or urine of infected hosts. Transmission can also occur by direct penetration of the leptospira organism through the conjunctiva or surface epithelium.